International Business.Development of entrepreneurship and business environment - Sharipov O’gabek Ziyodullaevich; Avulov Shaxzod Erkinovich (Peerian Journals Publishing, 2022)
This article talks about small business, private entrepreneurship, ongoing business development reforms in Uzbekistan and their statistics, international business, the development of international business and its levels, obtaining an international business level.
Keywords: entrepreneurship; international business; small business; doctoral degree